Circularly polarized soft X-ray generation by Co/Pt thin film polarizer with perpendicular magnetic anisotropy - Lee, Sang-Hyuk; Huang, Lin; Lee, Jae-Woong; Kim, Namdong; Shin, Hyun-Joon; Jeong, Jong-Ryul; Hwang, Chanyong; Kim, Dong-Hyun (Current applied physics, 2018)
We have experimentally demonstrated circular polarization generation from linear polarized soft X-ray at synchrotron by adopting a thin magnetic film polarizer. Polarizer is composed of Co/Pt multilayer with a perpendicular magnetic anisotropy, which allows us to easily accommodate without needing any tilting angle into the measurement setup since the circular polarization is generated for the X-ray with normal incidence and transmission. Generated circular polarization is examined by observing magnetic domain features based on the X-ray magnetic circular dichroism, where ∼11% of circular component is estimated compared to the case of full circular polarization.